Clinical applications of antineutrophil cytoplasmic antibody testing - Schmitt, Wilhelm; Woude, Fokko J. van der (Current opinion in rheumatology, 2004)
Purpose of review: Antineutrophil cytoplasmic antibodies are closely associated with Wegener granulomatosis, microscopic polyangiitis, and Churg-Strauss syndrome and have contributed to new pathogenetic concepts and improved nomenclature of systemic vasculitides (antineutrophil cytoplasmic antibody-associated vasculitides). However, the application of antineutrophil cytoplasmic antibody testing as a clinical diagnostic tool is still regarded as controversial. This review summarizes the most recent developments in the field, identifies areas of uncertainty, and gives practical guidelines. Recent findings: The problems of antineutrophil cytoplasmic antibody testing include the diversity of antineutrophil cytoplasmic antibody target antigens, assay standardization and performance, the application of antineutrophil cytoplasmic antibody testing in a clinical setting with a low pretest probability, and, finally, the widespread assumption that antineutrophil cytoplasmic antibody titers alone may closely reflect disease activity and therefore may be used to guide therapy. Summary: Recent findings demonstrate that the combined use of indirect immunofluorescence tests and solid phase assays to detect antineutrophil cytoplasmic antibody directed against myeloperoxidase and proteinase 3 can minimize the occurrence of false-positive antineutrophil cytoplasmic antibody results. Furthermore, the yield of antineutrophil cytoplasmic antibody testing can be improved by the use of a well-standardized test, adherence to published guidelines, and restricting the use of the tests to clinical situations with a rather high pretest probability for antineutrophil cytoplasmic antibody-associated vasculitides. However, treatment decisions should be based on the clinical presentation of the patient and histologic findings and not on the results of antineutrophil cytoplasmic antibody testing alone.